Association between oxidative balance score and glaucoma in the National Health and Nutrition Examination Survey - Jun Huang; Yulan Zhang; Chao Wu; Yifan Wu; Feiran Wang; Yunxuan Ning; Lu Shi (Frontiers in Nutrition)
ObjectiveTo investigate the association between Oxidative Balance Score (OBS) and glaucoma risk.MethodsUsing data from the National Health and Nutrition Examination Survey (2005–2008), we analyzed 2,615 participants aged ≥40 years. OBS was calculated from 15 antioxidant and 5 pro-oxidant components, including dietary nutrients and lifestyle factors. Glaucoma was identified through self-reported diagnosis and retinal imaging. Survey-weighted logistic regression and restricted cubic splines (RCS) were used to assess associations.ResultsHigher OBS was associated with lower glaucoma risk (adjusted OR = 0.97, 95% CI: 0.94–1.00). Participants in the highest OBS quartile showed 51% lower odds of glaucoma compared to the lowest quartile (adjusted OR = 0.49, 95% CI: 0.27–0.90). The protective effect was more pronounced among middle-aged adults (40–60 years; OR = 0.90, 95% CI: 0.86–0.95) and males (OR = 0.93, 95% CI: 0.90–0.97).ConclusionHigher OBS were associated with lower glaucoma prevalence, particularly among middle-aged adults and males, suggesting potential benefits of maintaining oxidative balance in glaucoma prevention.